Maximal pulmonary ventilation and lactate affect the anaerobic performance in young women exposed to hypobaric hypoxia - Páez, Valeria; Rodriguez-Fernandez, Maria; Silva-Urra, Juan; Núñez-Espinosa, Cristian; Lang, Morin (Frontiers in Physiology, 2023)
Background: Athletes, tourists, and mining workers from all over the world ascend daily to an altitude greater than 3.000 meters above sea level to perform different activities, all of which demand physical effort. A ventilation increase is the first mechanism once the chemoreceptors perceive the hypoxia and is key to maintaining blood oxygen levels during acute exposure to high altitude and to buffering lactic acidosis during exercise. It has been observed that gender is a variable that can influence the ventilatory response. Still, the available literature is limited due to the few studies considering women as study subjects. The influence of gender on anaerobic performance and its effects in high altitude (HA) environments have been poorly studied. Objective: The objectives of this study were to evaluate anaerobic performance in young women exposed to high altitude and to compare the physiological response to multiple sprints between women and men measured by ergospirometry. Methodology: Nine women and nine men (22,9±3,2 years old) carried out the multiple-sprint anaerobic test under two conditions, sea level and high altitude. Results: In the first 24 hours of exposure to high altitude, lactate levels were higher in women than men (2.57±0.4 Mmol/L, 2.18±0.3 Mmol/L, respectively; p<0.05). Secondly, women had a decreased ventilatory response in exposure to high altitude compared to men (p>0.005). Third, there is a positive correlation between lactate levels prior to an anaerobic test and the ventilatory response developed by subjects at high altitude (R2=0.33, slope=-41.7, p<0.05). Lastly, this ventilatory response can influence the VO2peak (R2=0.60, slope=0.02, p<0.001). Conclusion: This study provides insights into the mechanisms behind the reduced respiratory capacity observed in women during an anaerobic exercise test at high altitude. Acute response to HA showed a greater work of breathing and increased drive ventilatory response. It is possible to postulate differences in the fatigue-induced metaborreflex of the respiratory muscles and aerobic-anaerobic transition between gender. These results on multiple sprints performance and the influences of gender in hypoxic environments deserve further investigation.